Gas-Sensitive Characteristics of Low-Power Semiconductor Gas Sensors to CO and H2 - I. A. Taratyn; O. G. Reutskaya; G. G. Gorokh; I. V. Serdyuk; V. S. Fedosenko (Приборы и методы измерений)
Strict requirements for determining of gases concentration in the working environment it is relevant to develop of semiconductor sensors which provide rapid response and safety of personnel in industrial and domestic premises. The aim of the work was to study gas-sensitive and dynamic characteristics of high-sensitive low-power sensors made on thin nanoporous substrates with gas-sensitive layers of semiconductor metal oxides. The low-power semiconductor gas sensor on the anodic alumina substrate has been developed. Sensors with gas-sensitive semiconductor metal oxide layers based on In2O3+Ga2O3, In2O3+SnO2 and SnO2+Pd deposited from aqueous solutions with subsequent firing on sensor information electrodes are manufactured. Studies of gas-sensitive characteristics have shown that sensors with SnO2 films with the addition of Pd nanoparticles have maximum sensitivity of about 85 % and high response rate to 10 ppm H2 at 410 °C. The maximum sensitivity of 250 % to 10 ppm CO at 220 °C was shown by films based on In2O3+SnO2, the response time τ90 was 5 s, while the sensitivity of In2O3+Ga2O3 and SnO2+Pd was 30–50 % at 410–420 ºC. Semiconducting metal oxides In2O3+Ga2O3 (70 % at 420 °C) and In2O3+SnO2 (30 % at 250 °C) showed lower sensitivity to hydrogen, with response time τ90 = 20 s. The sensors power consumption in all measurements was 28–60 mW. Semiconductor gas sensors with low energy consumption can be used in the systems development that monitor the carbon monoxide concentration in the work area, as well as detect ignition's early stages.